(untitled) (Multidisciplinary Journal of Science and Technology, 2023)
The United Nations Universal Declaration of Human Rights was declared by the UN General Assembly with its resolution No. 217 (A) dated 10 December 1948. The importance of the declaration in terms of hate crimes is that all states have the obligation to protect together in order to prevent the violation of rights such as "life, personal security, freedom of thought and conscience" stipulated in the declaration through hate crimes. In this respect, states have to take some measures to protect these rights, one of the most effective of which is to prescribe a certain method of punishment. It should be noted that the Declaration is not binding. This article comprehensively organizes the list of human rights and plays a criterion role in terms of other binding international and regional agreements in the example of UN discourse